2453. Repeated Exposures to Minocycline/Rifampin and + Chlorhexidine Combination Used to Coat Catheters Fails to Induce Antimicrobial Resistance. (26th November 2018) - Vargas-Cruz, Nylev; Reitzel, Ruth; Rosenblatt, Joel; Hachem, Ray Y; Chaftari, Anne-Marie; Dib, Rita Wilson; Raad, Issam
Abstract: Background: Central venous catheters (CVC) impregnated with minocycline and rifampin (M/R) are recommended for use in high-risk patients to reduce catheter related bloodstream infections (CRBSI). We developed a second generation antimicrobial CVC with addition of chlorhexidine (CHD) for extended spectrum activity against virulent Gram-positive and Gram-negative bacteria as well as yeast. In this study we examined the potential for induced resistance with repeated exposure to M/R+CHD. Methods: Potential to induce resistance was evaluated by exposing a broad-spectrum of CRBSI pathogens to serial passages of sub-inhibitory concentrations of M/R+CHD and retesting MICs following each passage. Susceptibility to individual agents in the combination were assessed, to identify organisms that were originally resistant to the individual agents in the combination. A total of 24 Gram-positive, Gram-negative, and yeast pathogens were evaluated for baseline MICs following standard CLSI procedures. Subsequently, organisms that were exposed to one half the MIC were cultured and MICs retested. This process was carried out for a total of 21 passages to assess trends in MICs and potential for induction of resistance. Any organism with ≥4 fold increase in MIC were then passed in broth alone to assess phenotypic adaptation. Results: Synergy in the triple combination of M/R + CHD was detected for several resistant organisms that had low susceptibilities to the individual components but were highly susceptible to the combination. After a series of 21 passages, the organisms maintained the same MIC values as baseline with no clinically significant increases. One strain of Enterobacter showed a 4-fold MIC increase; however, the MIC returned to baseline after culturing in broth alone. Conclusion: Repeated exposure of M/R + CHD failed to show induced antimicrobial resistance among a large number of pathogens with both low and high susceptibilities. Furthermore, any increase in MIC returned to baseline with the removal of the stressor (M/R + CHD), indicating that the increase in MIC was a phenotypic adaptation rather than induced resistance. Surveillance studies assessing development of resistance will need to be conducted in a clinical setting. Disclosures: I. Raad, The University of Texas MD Anderson Cancer Center: Shareholder, Licensing agreement or royalty. The University of Texas MD Anderson Cancer Center: Shareholder, Dr. Raad is a co-inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed to Novel Anti-Infective Technologies LLC, in which UTMDACC and Licensing agreement or royalty.